2016
DOI: 10.1682/jrrd.2015.03.0042
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the 8-Foot Up and Go, Timed Up and Go, and Activities-Specific Balance Confidence Scale in older adults with and without cognitive impairment

Abstract: Abstract-The purpose of this study was to determine whether (1) mild cognitive impairment (MCI) alters the validity of the Timed Up and Go (TUG), the 8-Foot Up and Go (8UG), or the Activities-Specific Balance Confidence (ABC) scale in the identification of fallers and nonfallers and (2) there were differences in the concurrent validity between the TUG and ABC when compared with the 8UG and ABC in those with and without MCI. The classification of MCI was based on a score of <26 points on the Montreal Cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 20 publications
0
30
0
5
Order By: Relevance
“…The SMD is often used when studies assess the same outcome but measure it in a variety of ways; however, it may be inappropriate to use different, albeit similar tests of physical fitness interchangeably unless equivalence has been demonstrated. This is because successful performance may be determined by different physiological parameters and issues such as reliability and test sensitivity may vary [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMD is often used when studies assess the same outcome but measure it in a variety of ways; however, it may be inappropriate to use different, albeit similar tests of physical fitness interchangeably unless equivalence has been demonstrated. This is because successful performance may be determined by different physiological parameters and issues such as reliability and test sensitivity may vary [28].…”
Section: Methodsmentioning
confidence: 99%
“…Studies required to contain at least one of the following outcome measures to be included in this meta-analysis: (1) peak oxygen uptake ( V O 2peak ) or maximal oxygen uptake ( V O 2max ), assessed via maximal incremental test—associated with the ability to maintain independent function and prevent disability [4, 5]; (2) six-minute walk test (6MWT)—a valid and reliable measure of physical endurance associated with self-reported functional ability with performance determined by leg strength and power [29, 30]; (3) 8-ft timed up-and-go (TUG)—a composite measure of performance related to dynamic balance and mobility measured over a distance of 8 ft [31]. We selected the 8-ft distance as previous authors [31] have suggested that this version of the test can be more feasibility administered in a home setting, is simpler for participants to perform, and has better sensitivity than alternative versions [28]; (4) 30-s chair stand—a valid measure of lower body muscle functioning [32] capable of detecting change in functional capacity in older adults [33]. Assessment of functional fitness (e.g., 30-s chair stand, TUG) provides a composite measure of physical capability as successful performance on these tests is determined by several factors [34], providing a functionally relevant and ecologically valid assessment of fitness.…”
Section: Methodsmentioning
confidence: 99%
“…This test was carried out by a physiotherapist and a trained research assistant. TUG has excellent intra-rater reliability in community-dwelling older adults (intra-class coefficient of 0.94) [ 32 ] and moderate to excellent validity in older adults with and without MCI (Pearson correlation 0.64–0.74) [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…TUG can be effectively considered as six subtasks (Figure 1A ): the sit-to-stand transition (SI-ST), walking 1 (away), turn 1 (180°), walking 2 (return journey), turn 2 (180°), and the stand-to-sit transition (ST-SI); in analyses, walking 1 and walking 2 are often bundled together because they represent nearly identical subtasks, and some analyses elide turn 2 with the ST-SI transition because the two subtasks usually do not have a clear boundary. A range of TUG-like variants also exist that shorten the walk [8-UG ( 25 )] or lengthen it [to 7 m each way ( 26 )] in order simplify the task for patients or to make the walking data more robust.…”
Section: Introductionmentioning
confidence: 99%